Short-term efficacy of 1-month and 3-month gonadotropin-releasing hormone agonist depots in girls with central precocious puberty - Min Jin Jeon (Annals of Pediatric Endocrinology & Metabolism, 2021)
Purpose Gonadotropin-releasing hormone agonist (GnRHa) has been the mainstay of central precocious puberty (CPP) treatment for decades, but few reports have compared the efficacy of 1-month and 3-month depot GnRHa formulations. This study investigates the short-term efficacy of 1-month and 3-month GnRHa depots in girls with CPP. Methods Overall, 150 girls with CPP were included in a retrospective review of medical records. Subjects in group 1 (n=105) were treated with 1-month GnRHa depots for ≥12 months, and those in group 2 (n=45) were treated with 1-month GnRHa depots for 6 months followed by 3-month GnRHa depots for ≥6 months. Anthropometric and biochemical data were compared between the groups at 3-time points (after 0, 6, and 12 months of GnRHa treatment). Results Demographic and clinical characteristics did not differ between the groups at baseline or after 6 months of GnRHa treatment. After 12 months of GnRHa treatment, patients in the both groups showed no difference in bone age (BA), chronological age (CA), BA–CA difference, height standard deviation score (SDS) for CA and BA, or body mass index SDS for CA and BA. The sexual maturity rate of the breast was prepubertal at 12 months in most of subjects. GnRH-stimulated luteinizing hormone (LH) level was suppressed during GnRHa treatment in both groups at 6 and 12 months, although the LH level in group 2 was higher than that in group 1. Conclusions Treating CPP with a 3-month GnRHa depot showed short-term efficacy comparable to that with a 1-month depot in anthropometric parameters and pubertal suppression.